Screening two biodegradable polymers in enhanced efficiency fertiliser formulations reveals the need to prioritise performance goals. (15th February 2022) - Redding, M.R.; Witt, T.; Lobsey, C.R.; Mayer, D.G.; Hunter, B.; Pratt, S.; Robinson, N.; Schmidt, S.; Laycock, B.; Phillips, I.
Abstract: Enhanced efficiency fertilisers (EEF) may reduce nitrogen (N) losses and improve uptake efficiency through synchronising N release with in-season plant requirements. We hypothesised that EEF formed via matrix encapsulation in biodegradable polymers will improve N use efficiency when compared to conventional urea fertiliser. This hypothesis was investigated for two biodegradable polymer matrices: polyhydroxyalkanoate (PHA), containing 11.6% urea (by mass), and polybutylene-adipate- co -terephthalate (PBAT), containing either 19.4 or 32.7% urea; and two contrasting soil types: sand and clay. Nitrogen availability and form was investigated under leaching conditions (water) with a growth accelerator pot experiment involving a horticultural crop and novel non-destructive three-dimensional scanning to measure in-season biomass development. The PBAT 32.7% formulation enabled greater above ground biomass production at both 50 and 100 kg N ha −1 equivalent application rates compared to conventional urea. For the sandy soil, plant scanning indicated that improved uptake performance with PBAT 32.7% was probably the result of greater N availability after 25 days than for conventional urea. Two of the encapsulated formulations (PHA and PBAT 19.4%) tended to decrease nitrogen leaching losses relative to urea ( P < 0.05 for the red clay soil). However, decreased N leaching loss was accompanied by poorer N uptake performance, indicative of N being less available in these biopolymer formulations. A snapshot of nitrous oxide emissions collected during peak nitrate concentration (prior to planting and leaching) suggested that the biopolymers promoted N loss via gaseous emission relative to urea in the sandy soil ( P  < 0.05), and carbon dioxide emissions data suggested that biopolymer-carbon increased microbial activity ( P < 0.1 ). Controlled testing of N release in water was a poor predictor of biomass production and leaching losses. The diverse behaviours of the tested formulations present the potential to optimise biopolymers and their N loadings by taking into account soil and environmental factors that influence the efficient delivery of N to target crops. The greater N uptake efficiency demonstrated for the PBAT 32.7% formulation confirms our hypothesis that matrix encapsulation can enable better synchronisation of N release with crop requirements and decrease leaching losses. Highlights: We tested urea, co-extruded in biodegradable polymers, as novel N fertiliser. Quantification of N leaching, nitrous oxide emission, and weekly crop biomass. Urea in PBAT improved N uptake (up to 21%, 50 kg of N ha −1 ) over conventional urea. Improved synchronisation of N supply with crop requirements increased efficiency. Improving uptake, leaching, and nitrous oxide emission can be opposing goals.